Theory of Planned Behavior and Readiness for Change on Behavioral Intention and Actual Behavior of Farmers - Yulihardi, Yulihardi; Syaiful, Syaiful; Amrullah, Amrullah; Afrida, Afrida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
The aim of Research is implementing the Theory of Planned Behavior (TPB) in the Agricultural Sector which looks at the influence of TPB and Readiness For Change variables on intention for the sustainability of the sector. This type of research is quantitative research,. The technique of collecting research data through a questionnaire with a Likert scale with a sample of 85 people.The results of the study show that the Attitude Norm has a positive and significant effect on the variables Intention. Also Subjective Norm has a positive and significant effect on the variables Intention Behavior the variable Previced Behavior Control has a positive and significant effect on the variablesIntention Behavior, Readiness For Change has a positive and insignificant effect on the variables Intention Behavior. Intention Behavior has a positive and significant effect on the variables Actual Behavior.